The interface between health sector reform and human resources in health - Dussault Gilles; Rigoli Felix (Human Resources for Health, 2003)
Abstract The relationship between health sector reform and the human resources issues raised in that process has been highlighted in several studies. These studies have focused on how the new processes have modified the ways in which health workers interact with their workplace, but few of them have paid enough attention to the ways in which the workers have influenced the reforms. The impact of health sector reform has modified critical aspects of the health workforce, including labor conditions, degree of decentralization of management, required skills and the entire system of wages and incentives. Human resources in health, crucial as they are in implementing changes in the delivery system, have had their voice heard in many subtle and open ways – reacting to transformations, supporting, blocking and distorting the proposed ways of action. This work intends to review the evidence on how the individual or collective actions of human resources are shaping the reforms, by spotlighting the reform process, the workforce reactions and the factors determining successful human resources participation. It attempts to provide a more powerful way of predicting the effects and interactions in which different "technical designs" operate when they interact with the human resources they affect. The article describes the dialectic nature of the relationship between the objectives and strategies of the reforms and the objectives and strategies of those who must implement them.